Effect of the rear foot and back plate in the swiming start performance - Taladriz, S. (University of Granada, Spain, 2015)
Vortrag auf dem Young Experts Workshop - Swim Start Research" 2015 in Kassel mit einem Vergleich von Greif-, Schritt- und Kickstart.